Estimation of ambient dose equivalent rate with a plastic scintillation detector using the least-square and first-order methods-based G(E) function. (April 2023) - Hwang, Jisung; Kim, Junhyeok; Jeon, Byoungil; Ko, Kilyoung; Ko, Eunbie; Cho, Gyuseong
Abstract: Dose-rate monitoring instruments measure the ambient dose equivalent and hence are crucial for protecting workers from radiation exposure. Although plastic scintillation detectors (PSDs) are ideal equipment for dosimetry, they are rarely used owing to the lower detection efficiency than other scintillation detectors. In this study, we acquired ten types of G(E) functions to utilize a PSD in spectroscopic dosimetry using the least-square and first-order methods. The energy response of PSD was much improved in terms of dose evaluation. Highlights: Measurement of ambient dose equivalent using a plastic scintillation detector. Detector with an EJ-276G plastic scintillator coupled to a silicon photomultiplier. G(E) function obtained using the least-square and first-order methods. Ensemble G(E) function showed the most stable and superior performance.